1965
DOI: 10.1111/j.1365-2621.1965.tb01858.x
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Valencene to Nootkatone

Abstract: SUMMARY Nootkatone, an important flavoring constituent in grapefruit, has been synthesized from the sesquiterpene hydrocarbon valencene. Valencene, which is isolated from orange oil, was oxidized with tert‐butyl chromate to yield a sesquiterpene ketone having the same physical properties as the natural nootkatone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 5 publications
(2 reference statements)
0
27
0
Order By: Relevance
“…The largest fraction by weight, representing approximately 90% of all citrus oil compounds, is total monoterpene hydrocarbons (including d‐limonene; Hunter and Brogden 1965a). Other hydrocarbons present in orange peel oils include the sesquiterpenes, such as valencene (Hunter and Brogden 1965a, b). Previous findings also suggested that the fruity aromas in citrus oils, which are specific to different varieties, contain oxygenated terpenes (Stanley 1962).…”
Section: Other Important Components Of Citrus Fruitmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest fraction by weight, representing approximately 90% of all citrus oil compounds, is total monoterpene hydrocarbons (including d‐limonene; Hunter and Brogden 1965a). Other hydrocarbons present in orange peel oils include the sesquiterpenes, such as valencene (Hunter and Brogden 1965a, b). Previous findings also suggested that the fruity aromas in citrus oils, which are specific to different varieties, contain oxygenated terpenes (Stanley 1962).…”
Section: Other Important Components Of Citrus Fruitmentioning
confidence: 99%
“…Although representing a small portion of all citrus oils, esters, such as ethyl butyrate in orange essence, provide the characteristic aroma to citrus fruits (Wolford and others 1963; Ikeda and Spitler 1964; Shaw 1979). Terpene aldehydes and ketones are important flavoring constituents in lemons, oranges, and grapefruits (Stanley and others 1961; MacLeod Jr. and Buigues 1964; Hunter and Brogden 1965b). Other volatile flavoring constituents and citrus oils include alcoholic compounds, such as linalool and octanol, which are in trace amounts in lemon, lime, grapefruit, and tangerine (Attaway and others 1962; Hunter and Moshonas 1965; Hunter and Moshonas 1966).…”
Section: Other Important Components Of Citrus Fruitmentioning
confidence: 99%
“…Nootkatone is an oxidized sesquiterpene, which is obtained by the oxidation of (+) valencene (Figure a; Fraatz et al ., ). Valencene is present in various citrus species, for example in the essential oil of Valencia orange ( Citrus x sinensis ) (Hunter and Brogden, ,b). Valencene imparts a woody citrus characteristic and is economically important because it gives a juicy impression in citrus flavourings and fragrances.…”
Section: Introductionmentioning
confidence: 99%
“…Since grapefruit material is limited on the world market, synthetic (+)-nootkatone produced from (+)-valencene is predominantly used in commercial applications, also for the flavour market [5]. Chemical oxidation of valencene requires the use of tert-butyl chromate [6], which is a carcinogenic substance. Alternatively non-carcinogenic tert-butyl peracetate [7] or tert-butyl hydroperoxide can be used which are highly flammable and corrosive compounds.…”
Section: Introductionmentioning
confidence: 99%